Introduction: Is a Military Really Worth Having?. Issue 3 (2021) - Balint, Peter
Abstract: Just war theory has traditionally focused on jus ad bellum (the justice of war) and jus in bello (justice in war). What has been neglected is the question of jus ante bellum, or justice before war. In particular: Under what circumstances is it justifiable for a polity to prepare for war by militarizing? When (if ever) and why (if at all) is it morally permissible or even obligatory to create and maintain the potential to wage war? What are the alternatives to the military? And if we do have militaries, how should they be arranged, trained, and equipped? These considerations are not about whether war making is justified, but about whether war building is justified . In Ethics, Security, and the War-Machine, Ned Dobos argues that we have not sufficiently calculated the true (noneconomic) costs of the military, and that if we did, having a standing defense force would not seem like as good an idea. Dobos pushes us to reflect on something we have taken for granted: that one of the biggest institutions in our society, which is supposed to keep us safe and allow us to lead our own lives, may in fact pose great dangers and risks to us physically, morally, and culturally. The essays in this symposium take Dobos's work as a starting point and show the importance, complexity, and richness of this new strand of ethical inquiry.